Factors Associated with Hospital Admission in Patients with Acute Exacerbation of Chronic Obstructive Pulmonary Disease in a Teaching Hospital - Siddiqui, Md Nure Alom; Sultana, Shahnaj; Khan, MMR; Basak, PM (TAJ: Journal of Teachers Association, 2018)
Background: Acute exacerbations of chronic obstructive pulmonary disease (AE-COPD) impair quality of life (QOL), accelerate the decline in lung function and often require hospitalization, and thus, leading to increased healthcare burden. By identifying factors that may be associated with AE-COPD and managing them rationally, not only the hospital admissions could be avoided but progression of the disease may also be slowed. Objective. The aim of the present study was to determine the factors associated with hospital admissions among adults with AE-COPD. Methods. Seventy-three patients admitted with AE-COPD were administered a structured questionnaire during their hospital stay. Data on body mass index (BMI), smoking, symptoms, co-morbidities course of the disease, spirometry management and outcomes during the hospitalisation were obtained. Factors associated with hospital admissions were analyzed. Results. The hospitalization due to AE-COPD was significantly associated with the reduced forced expiratory volume in one second (FEV1), and peak expiratory flow rates, increasing sputum purulence, number of hospitalizations during previous year for COPD and presence of co-morbidities. Conclusions. The study shows that both disease and healthcare-related factors are predictors for hospitalisation. Identification of risk factors and appropriate management may reduce hospitalisation due to AE-COPD. TAJ 2015; 28(2): 52-57